Generation of ion cyclotron waves in the corona and solar wind. Issue 3 (14th March 2014) - Omidi, N.; Isenberg, P.; Russell, C. T.; Jian, L. K.; Wei, H. Y.
Abstract To examine the generation and nonlinear evolution of ion cyclotron waves in the corona and solar wind, we perform electromagnetic simulations using a wide range of plasma conditions and ion velocity distribution functions. The source of the instability is temperature anisotropy of ions with temperature perpendicular to the magnetic field larger than parallel. For velocity distribution we use Maxwellian, bi‐Maxwellian, and Fermi‐accelerated functions with perpendicular temperature larger than parallel with the aim to understand the extent to which the details of the distribution function impact the general properties and the nonlinear evolution of the instability. The results show that in a proton‐electron plasma, ion cyclotron waves are generated over a wide range of temperature anisotropies and plasma beta. Also, the general properties of the instability and the nonlinear evolution of the waves are not sensitive to the details of the velocity distribution functions. Allowing for the presence of minor ion species we show that these ions by themselves can drive the instability and generate waves with frequencies below the gyrofrequency of the minor ions. In the event that protons also have temperature anisotropy, waves on the proton branch are also generated. Results using bi‐Maxwellian or Fermi‐accelerated velocity distribution functions show similar properties for the instability and the nonlinear evolution of the waves. However, differences are found when allowing for relative drifts between the protons and minor ions in that when using Fermi‐accelerated distribution functions oblique ion cyclotron waves are generated that are not observed in simulations using bi‐Maxwellian distribution function.